Sensory Properties of Gluten-Free Biscuits Formulated with Cassava-Jicama Combined Flour and Various Fats - Lucia Crysanthy Soedirga; Richirose Richirose (Universitas Sebelas Maret (UNS), 2025)
Biscuits, a popular bakery item, usually contain wheat flour as a main ingredient, making them unavailable for gluten-sensitive consumers. This research aims to determine the effect of different formulations on the sensory characteristics of gluten-free biscuits. The research followed a randomized block design. The factor in this study was biscuit formulations (100:0, 90:10, 80:20, 70:30, 60:40,50:50). Determination of preferred formulation was done using the De Garmo method. The selected formulation was a gluten-free biscuit made with 90:10 cassava and jicama flour with shortening, namely F4. Panelists perceived F4 had no foreign aroma (2.20±1.18), no foreign taste (2.37±1.14), and no bitter aftertaste (2.57±1.17). The biscuit also does not have a hard texture (2.31±1.02) with a slightly not brown color (3.29±1.36). From the hedonic results, the panelists were slightly like the acceptance of foreign aroma (5.29±1.13), foreign taste (5.00±0.94), foreign aftertaste (5.00±1.19), color (5.20±1.28), and overall acceptance (5.06±1.11). Meanwhile, the panelist was neutral to accepting the biscuit’s hardness (4.71±1.93). Moreover, the result of the present study also aligned with the previous research, which conducted the objective measurement of the biscuits.